In vitro evaluation of the clinical utility of Apitolisib/Vorinostat combination in Apitolisib-resistant H1975 lung adenocarcinoma cells - Abduladim Hmmier; Paul Dowling (SpringerOpen, 2024)
Abstract Background The PI3K signalling pathway regulates the metabolic activity of cells. Disruption by PI3K inhibitors causes an aerobic/anaerobic imbalance that decreases energy production and cell growth. Cancer cells adapt to PI3K inhibitors in order to reduce their effectiveness. Resistance to Apitolisib could be due to intrinsic factors or acquired adaptation. Oncologists often ask whether to discontinue Apitolisib, increase its dose, or use a drug combination. Methods We observed the proliferation of resistant cells in (H1975R+) and out (H1975R−) of Apitolisib treatment, cell cycle pattern, energy phenotyping/reprogramming, and the effects of combining Apitolisib with Vorinostat on the acquired proliferation of H1975R− cells. Results The Proliferation of H1975R− cells increased, while that of H1975R+ cells remained suppressed. Both conditions showed a 5 × decrease in the number of cells at the Go/G1 phase and doubled at S and G2/M phases (p < 0.0001). Both H1975R− and H1975R+ cells exhibited decreased ECAR, with a stronger effect observed in H1975R+ cells (p < 0.0001). Oxygen consumption (OCR) increased significantly in H1975R− compared with that in H1975P (p = 0.02). The resistant cells became energetically active using mitochondrial respiration in drug-free medium; H1975R+ was hypo-energetic and consumed more free fatty acids (p = 0.0001). Ketone bodies in H1975R+ were increased by 40% and 2 × in BOHB and AcAc levels, respectively, compared to that in H1975P and H1975R− (p < 0.0001). H1975R− cell survival was 80% compared with 20% in H975R+ cells treated with 7 μM Vorinostat. Vorinostat effectively controlled acquired hyperproliferation of H1975R− cells. Conclusion If a tumour becomes unresponsive to Apitolisib, it is advisable to continue the inhibitor and consider a combination with non-tyrosine kinase inhibitors.